Implementasi Nilai Pendidikan Islam dan Gotong Royong dalam Kegiatan Pengabdian Pasca banjir hidrometeorologi di Aceh - Nasrullah Nasrullah (Yayasan Madinah Al-Aziziyah, 2025)
This study examines the implementation of Islamic education values and mutual cooperation in post-flood community service activities in Aceh. Floods as recurring hydrometeorological disasters cause not only physical damage but also social and spiritual impacts on affected communities. Therefore, post-disaster community service requires an approach that goes beyond technical assistance and emphasizes value-based practices. This study aims to analyze how Islamic educational values and mutual cooperation are implemented in post-flood community service and to identify their contribution to social recovery. The research employed a library research method by reviewing literature on Islamic education, social solidarity, and disaster studies. The findings indicate that Islamic values such as mutual assistance, brotherhood, and social care are manifested through collective community actions. However, these practices remain largely spontaneous and lack a structured model. This study concludes that post-disaster community service based on Islamic values and local culture has strong potential as an effective and sustainable social recovery model in Aceh.